Analisis Ekonomi Islam Terhadap Implementasi Harga Eceran Tertinggi (HET) Dalam Penjualan Obat Generik Pada Apotek di Kelurahan Tangkerang Tengah Pekanbaru - Antoni, Feri; Oktavianti, Rika; Adriansyah, Henry Martin (EL-EMIR Institute, 2024)
The Indonesian government always strives to improve public health by launching generic drugs as alternative drugs for the public with guaranteed quality, affordable prices, and sufficient drug availability. So that the public can obtain correct information about generic drugs and their prices, labeling of generic drugs has also been carried out on the packaging, and the Highest Retail Price (hereinafter referred to as HET) has been included in this article. With this background, researchers formulated problems including, how to analyze Islamic Economics in Implementing the Highest Retail Price (HET) in the Sale of Generic Medicines at Pharmacies in Tangkerang Tengah Subdistrict Pekanbaru. The type of research used in this research is field research and was carried out using a qualitative descriptive approach using several data collection techniques, namely, observation, interviews and documentation. The population in this study consisted of 12 pharmacies and drug stores in Central Tangkerang, while the samples taken were 4 people. Based on the research results, it can be concluded that in the implementation of sales of generic drugs exceeding the Highest Retail Price (HET), the majority of consumers feel that they do not know that there is a highest retail price in each generic drug package and that government supervision is weak, which has not carried out supervision regarding the highest retail price and in view Islamic law shows that selling generic drugs above the highest retail price is an act that is not permitted because the price given by the seller to consumers does not match the price that has been set or the highest retail price.